Detection of Homologue and Isomer Vapors through Dynamic Reflection Spectra of Hollow Mesoporous Silica Sphere Photonic Crystals. Issue 23 (24th October 2018) - Xiong, Chengjia; Pan, Mengyao; Wang, Lebin; Geng, Hongbin; Zhao, Jiupeng; Li, Yao
Abstract: Vapors of homologues and isomers with very similar refractive indices can be easily distinguished by using dynamic reflection spectra (DRS) of hollow mesoporous silica sphere (HMSS) photonic crystals (PCs). Different diffusion behaviors render the HMSS PCs with a distinct response to different chemicals vapors, leading to diversity in the evolution of the reflection spectra and their DRS patterns. Therefore, by studying the geometric characteristics and color changes of color‐filled contour maps, as well as the reflection peak shift speeds at different stages, even isomers such as n ‐butanol and iso ‐butanol, with a refractive index difference of only 0.001, can be recognized. The reflection peak shift speed depends on both the refractive index and the diffusion speed of chemicals. The proposed strategy provides a convenient, accurate, and low‐cost method to detect vapors of homologues and isomers. Abstract : The dynamic reflection spectra (DRS) method based on HMSS PCs shows a high selectivity and sensitivity for the detection of chemicals with very similar refractive indices.